Work and childcare : implementing the Council recommendation on childcare: a guide to good practice. (Employment and social affairs, 1996)
Working and caring - Reconciling work and family responsibilities - What needs to be done? Policies and good practice - How can it be done? - Is it Working? Monitoring, evaluation and review - The Council recomendation on Childcare 1992 - Commission Policy on Reconciliation: Related Law, Structural Funds and Community Initiatives - Glossary of key concepts - Framework on Reconciliation - Who Benefits? -